Reptilia, Squamata, Serpentes, Viperidae, Bothrops lutzi: distribution extension, geographic distribution map. - Loebmann, Daniel [UNESP] (2009)
Universidade Estadual Paulista, Instituto de Biociencias, Laboratorio de Herpetologia, Avenida 24 A, 1515, Bairro Bela Vista, CEP 13506-900, Rio Claro, SP, Brazil